Delivery of a TNF‐α–derived peptide by nanoparticles enhances its antitumor activity by inducing cell‐cycle arrest and caspase‐dependent apoptosis. Issue 12 (30th August 2018) - Yan, Qiuxia; Chen, Xueming; Gong, Huizhen; Qiu, Pei; Xiao, Xing; Dang, Shiying; Hong, An; Ma, Yi
ABSTRACT: Prostate cancer is the second‐most common malignancy of the male genitourinary system. TNF‐α has attracted intense attention as a potential therapeutic agent against various cancers. However, its therapeutic application is restricted by short half life and severe toxic side‐effects. In this study, we constructed a stable nanodrug called TNF‐α–derived polypeptide (P16)‐conjugated, chitosan (CTS)‐modified selenium nanoparticle (SC; SCP), which is composed of SC as a slow‐release carrier conjugated to P16. SCP had significant inhibitory effects on multiple types of tumor cells, especially DU145 prostate cancer cells, but not on RWPE‐1 normal human prostate epithelial cells. SCP could induce G0 /G1 cell‐cycle arrest and apoptosis in DU145 cells more effectively than could P16 and TNF‐α. In DU145 xenograft tumor models, SCP exerted much stronger antitumor effects than P16 or estramustine (the clinical drug for prostate cancer) but caused fewer toxic side‐effects. In addition, SCP significantly inhibited proliferation and accelerated apoptosis in DU145 xenograft tumors. Further mechanistic studies revealed that SCP exerted antitumor effects via activation of the p38 MAPK/JNK pathway, thus inducing G0 /G1 cell‐cycle arrest and caspase‐dependent apoptosis. These findings suggest that SCP may represent a potential long‐lasting therapeutic agent for human prostate cancer with fewer side effects.—Yan, Q., Chen, X., Gong H., Qiu, P., Xiao, X., Dang S., Hong A., Ma, Y. Delivery of a TNF‐α–derived peptide by nanoparticles enhances its antitumor activity by inducing cell‐cycle arrest and caspase‐dependent apoptosis. FASEB J. 32, 6948–6964 (2018). www.fasebj.org